Case Report: Enhancing lead extraction techniques: a novel approach using a loop formed by an ablation catheter and a gooseneck snare - Li, Jun; Wang, Lei; Li, Xiaofang; Li, Na; Shao, Xin; Zhang, Anxin; Shu, Yan; Wang, Haixiong (Frontiers in Cardiovascular Medicine, 2024)
The difficulty and complexity of lead extraction procedures increase with the age of the lead to be extracted. The extraction of old (>20 years) leads is more time-consuming and requires advanced tools and a complex technique. In this case, we retrieved a very old (>30 years) lead using a loop formed by a catheter and a gooseneck snare. The catheter was rotated to remove the lead-bound sites. The lead was successfully retrieved using a Needle's Eye Snare.